Enhancing Neonatal Sucking Reflex: A Study on the Efficacy of Magnesium Sulphate in Severe Birth Asphyxia: Neonatal Sucking Reflex: Magnesium Sulphate in Severe Birth Asphyxia - Akram, Muhammad; Malik, Abdur Rehman; Ahmad, Munir; Arshad, Rana Tashfeen (Pakistan Journal of Health Sciences, 2025)
One of the main causes of prenatal deaths and a known factor in neuromotor disabilities is perinatal asphyxia. Objectives: To compare the efficacy of magnesium sulphate on the appearance of a good sucking reflex in cases of birth asphyxia with controls (without magnesium sulphate). Methods: This randomized controlled trial was conducted at the Department of Neonatology, The Children’s Hospital and the Institute of Child Health, Multan, from January 2024 to June 2024. A total of 80 full-term newborns of both genders with severe birth asphyxia admitted within six hours of life were randomly assigned to either the study group or the control group. The study group received 3 doses of magnesium sulphate 24 hours apart by intravenous infusion at 250 mg/kg/dose, and the control group did not receive this treatment. Supportive care was given to both study groups. Both groups were examined for sucking reflexes. Results: 46 (57.5%) were male, while 43 (53.8%) had a body weight of ≥2.5 kg. The mean age at the time of presentation was 3.2 ± 1.5 hours. Overall efficacy was observed in 48 (60.0%) babies. The distribution of efficacy in terms of the appearance of a good sucking reflex was significantly better in the magnesium sulphate group versus the control group (75.0% vs 45.0%, p=0.0062). Conclusions: It was concluded that magnesium sulfate was found to significantly improve the appearance of a good sucking reflex among newborns with severe birth asphyxia, highlighting its potential as a neuroprotective intervention in neonatal care.